A Case of Ruptured Exophytic Uterine Artery Pseudoaneurysm without Specific Risk Factors That Manifested Seven Days after Vaginal Delivery - Masatake Toshimitsu; Takayuki Iriyama; Jiro Sato; Osamu Abe; Mari Ichinose; Seisuke Sayama; Takahiro Seyama; Kenbun Sone; Keiichi Kumasawa; Yutaka Osuga (Case Reports in Obstetrics and Gynecology)
A uterine artery pseudoaneurysm (UAP) is a life-threatening complication during pregnancy and postpartum. Early diagnosis of exophytic UAP rupture is difficult due to the absence of vaginal bleeding. This study reports the case of a 31-year-old postpartum woman who presented with abdominal pain and fever seven days after vaginal delivery, without symptoms of maternal shock. Ultrasonography revealed a ruptured exophytic UAP with hemoperitoneum, which was confirmed using computed tomography. Interventional radiology confirmed that the site of the pseudoaneurysm was at the level of the uterine artery bifurcation, and embolization was performed immediately after diagnosis using a coil and n-butyl-2-cyanoacrylate. The patient’s symptoms were relieved, and she was discharged 12 days after the embolization. At eight months postpartum, the UAP was not visible on transvaginal ultrasonography. Exophytic UAP can occur even in the absence of specific risk factors such as cesarean section or endometriosis, and the UAP may not necessarily rupture immediately after delivery. Obstetricians must remain aware of the possibility of exophytic UAP rupture manifesting as abdominal pain with postpartum fever, rather than as unstable vital signs. This is the first report of an exophytic UAP that occurred at the level of the uterine artery bifurcation. Identification of the sites where exophytic UAP can occur can aid in the early diagnosis of the condition.